Sangkaan Fraktur 1/3 Distal di Rumah Sakit Umum Haji Medan - Tarigan, Liberti; Tambunan, Justinus (Health Information : Jurnal Penelitian, 2023)
Os Femur radiography with suspected distal 1/3 fracture to show the fracture and abnormalities found in the Os Femur. The femur has the function of supporting and supporting the body, as a place of attachment for large muscles, and as a place for the production of red blood cells in the bone marrow. Fractures of the Os Femur are more often caused by forced injuries which often occur in traffic accidents where the patient experiences decreased consciousness and active bleeding occurs. At this writing, the examination projections used are Antero-Posterior and Lateral projections. The aircraft used by General X-Ray uses 200 mA. Image recording using Computed Radiography (CR). This research was conducted at the Haji Medan General Hospital with qualitative and descriptive research. Data collection was carried out by interviews, documentation and direct photography in the field. The conclusion from the results of the X-ray examination of the femur is a diaphyseal fracture of the distal 1/3 of the femur in the contrast position, the alignment is not good, which is shown using Antero-Posterior and Lateral projections and using Computed Radiography (CR) film processing so as to provide clear image results. optimal for diagnosing diseases and disorders.